Nucleotide sequences of CAZ-2, CAZ-6, and CAZ-7 beta-lactamase genes. - Chanal, C (1992)
CAZ-2, CAZ-6, and CAZ-7 are plasmid-mediated beta-lactamases that are markedly active against ceftazidime. The corresponding structural genes were amplified by the polymerase chain reaction. Nucleotide sequences were determined by direct sequencing of the amplified products. Analysis of the nucleotide and the deduced amino acid sequences showed that CAZ-2, CAZ-6, and CAZ-7 are derived from TEM-2 by three, four, and two amino acid substitutions, respectively. All these substitutions are located at positions 102, 162, 235, 236, and 237 (Sutcliffe numbering), which are known to extend the substrate range of beta-lactamases. These substitutions are Lys-102, Ser-162, and Ser-236 in CAZ-2; Lys-102, Ser-162, Thr-235, and Lys-237 in CAZ-6; and Lys-102 and His-162 in CAZ-7. These results indicate that the nucleotide sequence of CAZ-2 is identical to that of TEM-8. The nucleotide sequence of CAZ-7 possesses the two mutations described in TEM-16 by the oligotyping method. In contrast, the combination of mutations encountered in CAZ-6 has not yet been described, and this enzyme was designated TEM-24.